2018
DOI: 10.3389/fphys.2018.01022
|View full text |Cite
|
Sign up to set email alerts
|

Tuning RGD Motif and Hyaluronan Density to Study Integrin Binding

Abstract: Well-controlled surfaces with immobilized substrates enable novel approaches to investigate specific aspects of biological processes related to cell adhesion or motility. A subset of integrins, cellular transmembrane glycoproteins, recognize the evolutionarily conserved tripeptide sequence RGD, and anchor cells to their surrounding proteins as well as mediate bidirectional signaling. In this study, the main question was how co-presentation of hyaluronan (HA), an essential component of the extracellular matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The -RGD-sequence is known as a cell-binding peptide sequence, and the engineered vesicles incorporating the AQP proteins can have integrins that selectively bind to specific RGD peptides in the extracellular matrix. [21,22] -RGD-peptides tethered on the substrate can bind with the integrin of the vesicles, boost the AQP loading to the substrate, and enhance mechanical durability under high-pressure RO conditions. In this study, graphene oxide (GO) membranes were adopted as a substrate membrane because oxygen-containing functional groups on the GO surface can be easily modified with the desired peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The -RGD-sequence is known as a cell-binding peptide sequence, and the engineered vesicles incorporating the AQP proteins can have integrins that selectively bind to specific RGD peptides in the extracellular matrix. [21,22] -RGD-peptides tethered on the substrate can bind with the integrin of the vesicles, boost the AQP loading to the substrate, and enhance mechanical durability under high-pressure RO conditions. In this study, graphene oxide (GO) membranes were adopted as a substrate membrane because oxygen-containing functional groups on the GO surface can be easily modified with the desired peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Xu, H.M. et al found that ES-2 had good anti-angiogenetic activity in vitro , but its activity in vivo was moderated 28. In order for ES-2 to target tumor tissues, Xu and her colleagues designed AP25 by connecting RGD-4C (RGD-4C contains four cysteines, which form two disulfide bridges and confer the molecule higher stability 29,30) and ES-2. AP25 targets integrin αvβ3 and α5β1 on the surface of vascular endothelial cells and several animal experiments showed that it has significant anti-tumor effect 1-3.…”
Section: Discussionmentioning
confidence: 99%
“…It is present in various proteins of the extracellular matrix, including fibronectin, vitronectin, and fibrinogen. This tripeptide motif has a strong affinity towards integrins, the transmembrane glycoproteins involved in anchoring cells to the extracellular matrix [ 32 ]. It is known that integrins are expressed in various types of cells including leukocytes [ 33 ], macrophages [ 34 ], endothelial cells [ 35 ], and bone cells [ 36 , 37 ].…”
Section: The Enhancement Of Cpcmentioning
confidence: 99%